Pengaruh Kinerja Keuangan Daerah Terhadap Belanja Modal Pada Kabupaten/Kota Se-Bakorwil Madiun - Nurharibnu Wibisono; Mintarti Indartini; Endang Edi Rahayu (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2021)
The goals of its research was to decide the impact of Regional Financial Independence (KKD), the effect of Fiscal Decentralization (DF), the effect of PAD Effectiveness, also Regional Financial Efficiency (EKD) to Capital Expenditures (BM) partially and generally. The study data derive the Regency and City APBD in the Madiun Bakorwil 2014-2019, namely Madiun Regency, Magetan Regency, Ngawi Regency, Ponorogo Regency, Pacitan Regency, also Madiun City. The method of data analysis used multiple regression by SPSS V-20. The output indicated that KKD had an effect on BM, DF had an effect on BM, PAD Effectiveness had no effect on BM, EKD had an effect on Capital Expenditures. The adjusted R 2 value is 0.408, meaning that the influence of the KKD, DF, PAD Efficiency and KD Effectiveness variables on Capital Expenditures is 41% while the residual 59% is affected by outside of other variables not checked in this research.